Effect of polyhedral oligomeric silsesquioxane nanocage on the crystallization behavior of PEG5k‐b‐P(MA‐POSS) diblock copolymers achieved via atom transfer radical polymerization. Issue 4 (21st January 2019) - Ullah, Asad; Ullah, Shakir; Mahmood, Nasir; Shah, Syed M.; Hussain, Zakir; Hussain, Hazrat
Abstract : We report our findings on the effect of polyhedral oligomeric silsesquioxane (POSS) nanocages, incorporated into the block copolymer structure with poly(ethylene glycol) (PEG) via atom transfer radical polymerization, on the crystallization behavior of PEG‐ b ‐P(MA‐POSS) diblock copolymers. The PEG, which is a highly crystalline polymer, could no longer retain its crystalline nature when connected with long bulky POSS segments as confirmed by various tools including differential scanning calorimetry (DSC), polarized optical microscopy (POM), and wide and small angle X‐ray diffraction (WAXD and SAXD). The WAXS and SAXD investigations revealed that the PEG‐ b ‐P(MA‐POSS) block copolymers with higher POSS content phase separate into a disordered state with amorphous PEG and POSS crystalline domains. The temperature dependent (20°C‐90°C) WAXD or SAXD profiles of the block copolymers do not reveal any phase change. Thus, it could be argued that the POSS crystalline domains that retain their structural integrity during the heating and cooling cycles restrict the PEG chain mobility that hinders their crystallization. Nevertheless, in DSC data, even with higher POSS content, still the PEG melting and crystallization peaks could be seen, suggesting that PEG chains can still organize to form smaller crystalline domains that could not be detected by the POM and WAXD instruments. Abstract : The poly(ethylene glycol) crystallization is severely hindered after chain extension with polyhedral oligomeric silsesquioxane (POSS) segments in PEG‐ b ‐P(MA‐POSS) hybrid diblock copolymers. The POSS segments form crystalline domains that could survive the heat treatment (up to 90°C). The block copolymer with higher POSS content phase separates into a disordered state with predominantly amorphous PEG and crystalline POSS domains.